1987
DOI: 10.1523/jneurosci.07-03-00882.1987
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Ca2+ and K+ currents in bag cell neurons of Aplysia californica by dihydropyridine Ca2+ antagonists

Abstract: The effects of dihydropyridine calcium antagonists on whole-cell Ca2+ and K+ currents in the neurosecretory bag cells of the marine mollusc Aplysia californica have been investigated. Nifedipine and nisoldipine blocked bag cell Ca2+ currents with effects similar to those seen previously on Ca2+ currents in cardiac muscle: both compounds appeared to interact with Ca2+ channels when they were closed, open, and inactivated. Also, as seen in cardiac cells, nifedipine apparently binds with higher affinity to Ca2+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Newly formed myotubes also possess this 'K(ni) current (data not shown) but no similar current was observed in proliferating myoblasts (Hamann et al 1994 (Valmier, Richard, Devic, Nargeot, Simmoneau & Baldy, 1991). In Aplysia bag cell neurones, potassium currents are blocked with a Kd of 3-5 ,uM (Nerbonne & Gurney, 1987), similar to the Kd of nifedipine for the blocking of IK(dr) in prefused myoblasts. More recently, it has been shown that the A-current of bovine adrenal cells is also affected by DHP (Mlinar & Enyeart, 1994 (Zhao et al 1994).…”
Section: Discussionmentioning
confidence: 66%
“…Newly formed myotubes also possess this 'K(ni) current (data not shown) but no similar current was observed in proliferating myoblasts (Hamann et al 1994 (Valmier, Richard, Devic, Nargeot, Simmoneau & Baldy, 1991). In Aplysia bag cell neurones, potassium currents are blocked with a Kd of 3-5 ,uM (Nerbonne & Gurney, 1987), similar to the Kd of nifedipine for the blocking of IK(dr) in prefused myoblasts. More recently, it has been shown that the A-current of bovine adrenal cells is also affected by DHP (Mlinar & Enyeart, 1994 (Zhao et al 1994).…”
Section: Discussionmentioning
confidence: 66%
“…We found in previous voltage-clamp experiments that 10 HIM nitrendipine blocks about 90% of L-type current in sensory neurons (Eliot et al, 1993). Unlike their action in vertebrate neurons, dihydropyridine antagonists do not require depolarization to block Ca2+ currents effectively in Aplysia neurons (Nerbonne and Gurney, 1987;Edmonds et al, 1990).…”
Section: Pairing -Specific Facilitation In H7mentioning
confidence: 74%
“…The Ca 2ϩ current in Paramecium is unaffected by DHPs (43), and neuronal Ca 2ϩ currents in the hydrozoan jellyfish Polyorchis (21) and the flatworm Bdelloura (55) are only partially blocked by 10 -100 M nifedipine (although these Ca 2ϩ currents may not be gated by L-type channel homologues). Molluscs are the earliest organisms in which potent block of Ca 2ϩ currents by DHPs has been reported (56), although the current is unaffected by racemic BayK 8644. The present results demonstrate that the actions of DHPs, which are generally used to define a current as L-type, may not reliably identify L-type channel homologues in lower organisms.…”
Section: Cyca␣ 1 Represents An Early L-type Camentioning
confidence: 99%